Double faced buccal mucosal graft urethroplasty for near obliterative inflammatory urethral stricture: a retrospective study comparing two different techniques - Nagabhairava, Manu K.; Javali, Tarun; Kanishk, Dokania; Thimmegowda, Manasa; Sangle, Ameya R.; Patil, Amit (International Surgery Journal, 2024)
Background: Double-faced urethroplasty offers improved outcomes for the management of complex urethral strictures. In our study, we compared two different techniques of double faced buccal mucosal graft (BMG) urethroplasty. Methods: 46 patients who underwent double faced BMG urethroplasty at Ramaiah Medical College were retrospectively reviewed and grouped into A (Enzo Palminteri technique) and B (Joel Gelman technique). Post operatively, patients were followed up with AUA-SS, uroflowmetry and postvoid residual assessment. The data analysis was done using the statistical package for the social sciences (SPSS) version 21.0. A p<0.05 was considered statistically significant. Results: 24 patients belonged to group A and 22 patients belonged to group B. The mean stricture length measured was 4.42±1.632 cm in group A and 4.11±1.634 cm in group B with the preoperative mean Qmax and AUA score was 7±1.318 ml/s and 19.75±3.286 in group A and 7.3±1.497 ml/s and 18.68±3.469 in group B. Mean operative time was 162.7±12.156 minutes versus 181.36±7.429 minutes. Group A patients had significant intraoperative blood loss. Recurrence was noted in two patients, one from each group. Mean Qmax and mean AUA score at recent follow up was 19.3±1.63 ml/s and 6.4±2.10 versus 19.8±1.59 ml/s and 6.6±2.03 for group A and group B with a mean follow up of 36.6±12.63 months and 36.8±11.48 months respectively. Conclusions: Double faced BMG urethroplasty for near obliterative urethral stricture is safe, efficacious with ventral onlay associated with lesser operative time.